KONTRIBUSI KETERAMPILAN MANAJER SEKOLAH TERHADAP EFEKTIVITAS ORGANISASI SEKOLAH - Kusdiyanto, Heri; Indriatik; Nina Oktarina; Fathur Rokhman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the contribution of school managers to the effectiveness of school organizations, a case study at SMK Negeri 1 Batealit-Jepara. The principal, as a manager, plays a crucial role in managing human and material resources, and guiding all school members to achieve educational goals. This study focuses on three types of managerial skills: conceptual, human relations, and technical. Conceptual skills involve understanding the vision and mission and strategic decision making. Human relations skills emphasize the ability to collaborate, motivate, and communicate effectively. Technical skills include mastery of methods and techniques for managing school operations. Effective schools are defined as schools that achieve both academic and socio-emotional learning outcomes, with the support of visionary leadership, quality teachers, a positive learning environment, and parental and community involvement. This study uses a qualitative approach to describe how the principal managerial skills are implemented at SMK Negeri 1 Batealit-Jepara a literature review in realizing school effectiveness. The results of the study are expected to provide in-depth insight into the importance of principal managerial skills in the context of effective schools and contribute to the development of educational leadership practices.